One-pot sol–gel synthesis of Sr/Ca-doped silica nanoparticles for osteogenic therapy in osteoporosis - Palomeque Chávez, Juan C.; Mohammed, Ali A.; Aghajanpour, Sareh; Li, Siwei; Enzo, Stefano; Kelly, Nicole L.; Bradley, David G.; Kerherve, Gwilherm; Porter, Alexandra E.; Hanna, John V.; Jones, Julian R.; Pinna, Alessandra (Frontiers in Nanotechnology, 2025)
Osteoporosis affects more than 200 million people worldwide, with an osteoporotic fracture occurring approximately every 3 seconds; with ageing populations, its prevalence continues to rise, yet it remains under-diagnosed and under-treated. Strontium- and calcium-doped mesoporous bioactive glass nanoparticles (BGNPs) are promising due to their ability to combine bioactive bone-regenerative function with controlled therapeutic ion release. We optimized a one-step sol–gel (modified Stöber) synthesis by varying the solvent system (pure water vs. 1:1 ethanol/water) to control BGNP size and morphology and assessed their effects on pre-osteoblasts (MC3T3-E1). Characterization by electron microscopy, X-ray photoelectron spectroscopy, and ^29Si MAS NMR showed that ethanol inclusion yielded smaller, uniform spherical particles (74 ± 5 nm), whereas water alone produced significantly larger particles (224 ± 42 nm). Both Sr2+ and Ca2+ were incorporated as network modifiers within an amorphous silicate framework, with no crystalline phases. Cytocompatibility assays revealed a size-dependent response: larger particles reduced cell viability at 1 μg/mL, while both sizes were biocompatible at 0.1 μg/mL. At the non-toxic concentration of 0.1 μg/mL, BGNPs enhanced alkaline phosphatase activity, promoted osteogenic differentiation, and exhibited antioxidant activity by scavenging tert-butyl hydroperoxide-induced free radicals. These results indicate that solvent-controlled synthesis effectively tunes BGNP size without disrupting silicate network integrity, and that properly sized Sr/Ca-doped BGNPs support both osteogenic and antioxidant responses, making them strong candidates for advanced therapeutic approaches in osteoporosis treatment.